Avaliação da aplicação da clorexidina na resistência de união de sistemas adesivos convencionais. - Grande, Rodrigo Stanislawczuk (2008)
The aim of this study was to evaluate the effect of 2% chlorhexidine digluconate when in aquous solution or associated to the conditioner on the resin-dentin bond strength (BS) of etch-and-rinse adhesives. Forty-two, caries free, extracted molars were included in this study. The oclusal enamel of all teeth was removed with a slow-speed diamond saw, under copious water-cooling, in order to expose a flat surface.of dentin. In groups 1 and 2 (control – C), the surfaces were acid etched with conventional phosphoric acid and the adhesives Prime&Bond NT (PB) and Adper Single Bond 2 (SB) were applied after rinsing, drying and rewetting with water. In groups 3 and 4 (Ac/CHX) the same adhesives were applied in a similar maner, however a chlorexidine containing acid was previously applied. In groups 5 and 6 (CHX) the adhesives were applied according to the control group; however the rewetting procedure was performed with an aqueous solution of 2% of CHX during 60s. Composite build-ups (Opallis, FGM) were constructed incrementally and specimens were longitudinally sectioned in the “x” and “y” directions to obtain bonded sticks (0.8 mm2) to be tested in tension at 0.5 mm/min immediately or after 6 months of water storage. For the nanolakage investigation, 2 bonded sticks from each tooth were coated with nail varnish, placed in the silver nitrate and polished down with SiC paper. Resin-dentin interfaces were analyzed in a Scanning electron microscope. The BS data from each adhesive was submitted to a two-way repeated measures ANOVA and Tukey’s test (α=0.05). Both adhesives from the control groups showed reduction on the resin-dentin BS values after 6 months of water storage (p<0.05). When Ac/CHX or CHX was used, no reduction on the resin-dentin BS was observed. The nanoleakage pattern was more evident in the control than in the experimental groups. It was concluded that the use of CHX in an aqueous solution or associated with the conditioner was effective to reduce the degradation of resin dentin bonds after 6 months of water storage.